Strategic information management (SIM) among managers in Malaysian business environment / Norhayati Hussin - Hussin, Norhayati (Institute of Graduate Studies, UiTM, 2017)
Strategic Information Management (SIM) in an organization is sustained by significant factors. Without these factors, SIM ceased to exist, and therefore organization could not capitalize on the flexibility of information resources to develop innovative strategies to face the competitive environment. Not understanding what factors could contribute to SIM in an organizational context, many organizations have failed to capitalize their information resources strategically to assist them in their competition. With the fact that SIM is dependable on certain factors, it is only important that organization should determine, understand, and strategize the development of these factors. Strategic Information Management (SIM) occurs in an organization where managers utilize strategic information (SIU) with the purpose to formulate business strategies. To successfully use the strategic information, the managers must have a positive Information behaviour (IBM) with the support of Organizational Information Management Practices (OIMP) and Organizational Information Technology Practices (OITP) in an organization. It also needs the organization gives a better support in the management of information that acquires the process to create, organize, and distributing the Strategic Information. This thesis documents a study of the Strategic Information Use (SIU) and all factors associated to support managers for business strategy formulation. The premise upon which such a research initiative is founded concerns the subject is one of under-researched in information management topics, and this area is limited in scope and scale.